ANALISA DAMPAK PENGUMUMAN DIVIDEN TERHADAP RETURN, VARIABILITAS TINGKAT KEUNTUNGAN DAN AKTIVITAS VOLUME PERDAGANGAN SAHAM - Ratnawati - -; Sumiati - -; Iwan - Triyuwono (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT Â  Objective of this research is to ascertain whether the dividend announcement has impacts on return, security return variability and stock trading volume activity in the period surrounding the event. This research was conducted by using event study method with market adjusted model approach. The sample was 67 manufacturing companies announcing dividend between 2000-2001 and fulfilling sample criteria. The statistical test used is T-test: Paired Two Samples for Mean on the period before the event, at the moment of the event, and after the event. Statistical periods are applied to the extended periods (10 observation days) and abridged periods (5 observation days). Results indicate that dividend announcement significantly influence return, abnormal return on the period before-after announcement, while the security return variability is significant on the period before-at the moment of announcement and after-at the moment of announcement. The results of the research for the abridged periods indicate that dividend announcement significantly influence stock return on the period before-after announcement, and the security return variability on the period at the moment-after the announcement and before-after the announcement. The variables of cumulative abnormal return (CAR), security return variability (SRV) and trading volume activity (TVA) on the 10 and 5 observation days do not indicate any significant difference. Cumulatively, the research provides a conclusion that there is not sufficient informational content in the dividend announcement. This can be seen from the inconsistent results gained from some variables and which indicating that the form of Indonesian capital market, especially Jakarta Stock Exchange, is not semi strong efficient yet. This is seen from the significant results gained from the tests of some variables. Keywords: Dividend Announcement, Return, Abnormal Return, SRV, TVA